2017
DOI: 10.1515/pophzn-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Young Married Women’s Perceptions On The Maeanings And Motivations For Their Husbands’ Opposition To Their Modern Contraceptive Use In Malawi

Abstract: Abstract:The aim of the study was to examine the perceptions of young married women on meanings and motivations of partner opposition to their contraceptive use. Qualitative data was collected from focus group discussions and individual in-depth interviews with young married women and key informant interviews with health workers and traditional leaders in the districts of Ntcheu, Mangochi and Zomba in Malawi. Thematic data analysis was done using ATLAS ti software version 7. The results show that partners' opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Kaneka and Mturi (2017), in their further analysis regarding the abovementioned study, found that husbands' resistance to contraceptive use was related to their desire to exert control over the sexual and reproductive lives of their wives. Non-use of contraceptives would reduce women's extramarital sexual activities and make them less attractive to other men because of frequent child bearing [13].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Kaneka and Mturi (2017), in their further analysis regarding the abovementioned study, found that husbands' resistance to contraceptive use was related to their desire to exert control over the sexual and reproductive lives of their wives. Non-use of contraceptives would reduce women's extramarital sexual activities and make them less attractive to other men because of frequent child bearing [13].…”
Section: Discussionmentioning
confidence: 98%
“…A qualitative study in Ntcheu, Mangochi and Zomba districts found that unsupportive husbands made women to use contraceptive secretly [12]. Husbands' resistance was related to their desire to exert control over the sexual and reproductive lives of their wives [13]. Yeatman and Trinitapoli (2008) found that contraceptive acceptance differed per denomination in Malawi, with Catholic leaders showing least and Muslim and Pentecostal leaders showing most acceptance of contraceptives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Male and female respondents frequently cited that men were the sole decision-makers of the household and women did not have much say in their choice for contraceptive use, despite family planning and child upbringing being seen as women's issues and responsibilities. This was reported in Malawi, Nigeria, Tanzania, Uganda and among Somali refugees in Ethiopia (Aristide, et al Other reported reasons for resistance were the desire for men to exert power and control over the sexual and reproductive lives of their wives, and to prevent wives from engaging in extramarital sexual activities (Kaneka & Mturi, 2017). In Uganda, women who use modern contraception are mocked for having few children and referred to as prostitutes or adulterers (Kabagenyi, et al, 2016).…”
Section: Gender Attitudesmentioning
confidence: 99%